Reliability of Three-Dimensional Micro-Computed Tomography Root Canal Analysis Using Drishti Software: A Pilot Study - Samsudin, Nurulaqmar Iwani; Kamaruzaman, Marlena; Jawami, Afiq Azizi (UI Scholars Hub, 2024)
In recent years, micro-computed tomography (micro-CT) has become a promising tool for non-destructive imaging and the study of root canal morphology in endodontics. However, the reliability of such analyses heavily relies on the accuracy and consistency of the software used for image processing. Objective: This study aims to investigate the reliability of two different micro-CT voxel sizes using open-source three-dimensional (3D) software (Drishti v3.0) used to identify and quantify the Apical Foramen (AF) and Apical Constriction (AC) in mandibular premolars. Methods: Eight mandibular premolars were divided into two groups, with four samples in each group. Samples were scanned using a ZEISS X-Radia 520 Micro-CT system with two different voxel sizes of 23 μm (Group A) and 17 μm (Group B), respectively. The micro-CT data were reconstructed and transferred to Drishti Software, and individual image rendering was performed to visualize the images for data analysis. The position and measurement of AF and AC to the anatomical apex were measured individually and independently by single operators. Results: The reliability of the measurements assessed using Intraclass Correlation Coefficients (ICCs) between two voxel sizes was excellent and on par with previous research. This pilot study suggested that results for voxel sizes of 23 μm and 17 μm were comparable. Both voxel size 3D images demonstrated excellent and high-quality visualization of the root canal configuration, lateral and accessory canals, apical deltas, major AF, and AC. Conclusion: It is feasible and reliable to visualize and analyze 3D micro-CT images using open-source software (Drishti v3.0). Both voxel sizes of 23 μm and 17 μm are recommended for use in root canal study.